An Autonomous Task Algorithm Based on Behavior Trees for Robot - Zhou, Haotian; Min, Huasong; Lin, Yunhan (2019 2nd China Symposium on Cognitive Computing and Hybrid Intelligence (CCHI), 2019)
This paper proposed an autonomous task algorithm based on Behavior Trees (BTs) for robot, which enabled robot to complete tasks autonomously in dynamic environment with understanding user's intention. Different from other advanced robotic systems, we proposed a unified representation model based on BTs. It achieved the process of transformation from abstract intention to robot specific operation and had been applied on robotic component of human-robot interaction and reasoning, task planning, execution. Then, the autonomous task algorithm was designed, which generated a plan according to the user's intention, map it into a BTs model and execute it. The plan could be updated dynamically through the status feedback of execution, iteratively accomplished a series of ordered actions to complete the task. We designed simulations and actual experiments respectively to verify the feasibility and practicality of our methods. The success rate of simulation and actual experiments were both 100%.